The Evaluation of the Effects of Zn, and Amino Acid-Containing Foliar Fertilizers on the Physiological and Biochemical Responses of a Hungarian Fodder Corn Hybrid - Brigitta Tóth; Makoena Joyce Moloi; Seyed Mohammad Nasir Mousavi; Árpád Illés; Csaba Bojtor; Lóránt Szőke; János Nagy (Agronomy, 2022)
The benefit of applying foliar fertilizers is that crops can uptake them faster than soil fertilizers. The aim of this study was to test and valuate the effects of one zinc (Zn) and two amino acids-containing (AS) foliar fertilizers on a fodder corn hybrid’s physiological and biochemical processes. The experiment was conducted in field conditions. The following parameters of a fodder maize hybrid were measured one, two, three, four, five, and six weeks after the treatments (WAT): physiological (relative chlorophyll content and the effectiveness of PSII); biochemical (activities of superoxide dismutase (SOD); ascorbate peroxidase (APX) and guaiacol peroxidase (POD); the concentration of malondialdehyde (MDA); and proline. The yield increased by 10%, 6%, and 10% at Zn, Zn+AS1, and Zn+AS2 treatments. The yield parameters, such as grain/cob and ear weight, were also significantly higher under the applied three treatments relative to the control. The relative chlorophyll content was significantly higher one, two, and four weeks after Zn-treatment, and some changes were also observed when Zn and amino acid-containing fertilizer were applied in combination. The latter sampling did not show any notable changes. In addition, the activity of SOD increased when Zn-containing fertilizer was applied, although the effect of AS-containing fertilizer did not show. There was a correlation between the SOD activity and some of the yield parameters. The increasing SOD activity indicated a higher yield (t/ha) and a higher cob weight.